Recent Advances of Magnetic Nanomaterials in Bone Tissue Repair - Fan, Daoyang; Wang, Qi; Zhu, Tengjiao; Wang, Hufei; Liu, Bingchuan; Wang, Yifan; Liu, Zhongjun; Liu, Xunyong; Fan, Dongwei; Wang, Xing (Frontiers in Chemistry, 2020)
The magnetic field has been proven to enhance bone tissue repair by affecting cell metabolic behavior. Magnetic nanoparticles are used as biomaterials due to their unique magnetic properties and good biocompatibility. Through endocytosis, entering the cell makes it easier to affect the physiological function of the cell. Once the magnetic particles are exposed to an external magnetic field, they will be rapidly magnetized. The magnetic particles and the magnetic field work together to enhance the effectiveness of their bone tissue repair treatment. This article reviews the common synthesis methods, the mechanism, and application of magnetic nanomaterials in the field of bone tissue repair.